2010
DOI: 10.1007/s10342-010-0402-3
|View full text |Cite
|
Sign up to set email alerts
|

Anthropogenic disturbance of natural forest vegetation on calcareous soils alters soil organic matter composition and natural abundance of 13C and 15N in density fractions

Abstract: In the last century, many calcareous soils in Castilla León (northwestern Spain) have been transformed from natural Quercus ilex forest to cropped land. Reforestation with Pinus halepensis has been taking place during the past 40 years. In order to obtain a better understanding of how these disturbances affect ecosystem functioning, we studied the quantity and quality of soil organic matter (SOM) in natural forest ecosystems, cropland and Pinus plantations. Density fractionation combined with ultrasonic disper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
5
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 67 publications
(78 reference statements)
3
5
1
Order By: Relevance
“…No differences in soil N were detected between pine plantations and their paired unplanted areas and the native forests. This contrasts with many other studies that confirm that N follows the same recovery pattern as SOC after agricultural abandonment and/or afforestation (Dunjó et al, ; Duguy et al, ; Llorente et al, ). Conversely, other studies have demonstrated that afforestation did not ameliorate the soil N with regard to other land uses such as croplands or abandoned fields (Romanyà et al, ) so that most of this element in forest systems is found in the tree biomass (Rosenqvist et al, ).…”
Section: Discussioncontrasting
confidence: 93%
See 2 more Smart Citations
“…No differences in soil N were detected between pine plantations and their paired unplanted areas and the native forests. This contrasts with many other studies that confirm that N follows the same recovery pattern as SOC after agricultural abandonment and/or afforestation (Dunjó et al, ; Duguy et al, ; Llorente et al, ). Conversely, other studies have demonstrated that afforestation did not ameliorate the soil N with regard to other land uses such as croplands or abandoned fields (Romanyà et al, ) so that most of this element in forest systems is found in the tree biomass (Rosenqvist et al, ).…”
Section: Discussioncontrasting
confidence: 93%
“…Ruíz‐Navarro et al () showed that the influence of afforested pines (planted in terraces) on soil properties was minimal after 30 years and only a thin organic layer was found on the ground. On the contrary, authors such as Dunjó et al (); Llorente et al () or Fernández‐Ondoño et al () found improvements in the physical and chemical soil properties (the latest at catchment scale), and other works have shown no effects or weak positive effects on soil‐C inputs (Castillo et al, ; Nosetto et al, ).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…4a), was consistent with other studies (Piccolo et al 1994a;Lemma and Olsson 2006;Llorente et al 2010), and was presumably because processes affecting d 15 N (e.g. volatilisation and nitrification) were higher in the surface horizon (Piccolo et al 1994a).…”
Section: Full Soil Profile Samplessupporting
confidence: 82%
“…N along the chronosequences in this study were similar to those reported when forests have been converted to cropland (Lemenih et al 2005;Lemma and Olsson 2006;Awiti et al 2008;Llorente et al 2010). In those studies the increase in d N to an increase in soil N that was largely derived via N 2 fixation, and hence had a delta value of~0‰.…”
supporting
confidence: 75%